Undergraduate access to bibliographic databases: A comparison of descriptor dependent batch searching and online searching of ERIC. - Anholt, Elizabeth; Hurt, Howard (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
see PDF